Digitalization of Economy and Education: Path to Business Leadership and National Security - Vladyslav V. Novikov (Business Ethics and Leadership)
The article summarizes the areas of research on the integration of digitalization of the economy and education with the areas of business leadership and national security. The main purpose of the study is to determine the contextual characteristics that accompany the development of digitalization of the economy and digitalization of education and their impact on business development and the formation of national security. Existing theoretical and empirical research demonstrates meaningful links between the digitalization of education and the economy, business leadership and national security. The analysis showed that scientific interest in studying the digitalization of education and the economy continues to grow at the present stage, while research on national security and business leadership is currently declining. Bibliometric analysis shows that the relationship between the digitalization of the economy and education with business leadership can be traced in functional areas. On the other hand, the impact of the digitalization of the economy and education on national security can be identified by structural components. One should note that the evolution of scientific research is characterized by the transition from the study of individual structural elements and the penetration of digital technologies into the economy to identify areas for efficiency through digital and information technology. The analysis results provide a scientific basis for further research on key determinants of the effectiveness of the implementation of digital technologies in the economy and education, as well as the study of national security.